Os animais - Carraro, Adriana Pohl; Sumensari, Silvana Candelouro; Almeida, Gisele Rodriguês de; Emerick, Márcia Aparecida de Oliveira; Miotto, Jesuína Aparecida Gonçalves; Bordinhão, Andréia Jonceline Chiozini; Simião, Regina Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf